2002
DOI: 10.1161/hy0102.100780
|View full text |Cite
|
Sign up to set email alerts
|

Ang II Accumulation in Rat Renal Endosomes During Ang II-Induced Hypertension

Abstract: Abstract-Hypertension induced by long-term infusion of angiotensin II (Ang II) is associated with augmented intrarenalAng II levels to a greater extent than can be explained on the basis of the circulating Ang II levels. Although part of this augmentation is due to AT 1 receptor-dependent internalization, the intracellular compartments involved in this Ang II accumulation remain unknown. In the present study, we sought to determine whether Ang II trafficking into renal cortical endosomes is increased during An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
255
3
2

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 157 publications
(277 citation statements)
references
References 37 publications
17
255
3
2
Order By: Relevance
“…Our present data extend these findings demonstrating that chronic ARB treatment blocks the increases in kidney cortex AGT protein levels and urinary excretion rates of AGT. Thus, ARB treatment antagonizes both the enhanced internalization of circulating Ang II into kidney cells [15][16][17] and the stimulation of intrarenal AGT expression, [11][12][13][14] resulting in the amelioration of the enhanced intrarenal Ang II contents seen during chronic Ang II infusion. ARB treatment also blocked the Ang II-mediated inhibition of renin release leading to increased circulating Ang II levels.…”
Section: Discussionmentioning
confidence: 99%
“…Our present data extend these findings demonstrating that chronic ARB treatment blocks the increases in kidney cortex AGT protein levels and urinary excretion rates of AGT. Thus, ARB treatment antagonizes both the enhanced internalization of circulating Ang II into kidney cells [15][16][17] and the stimulation of intrarenal AGT expression, [11][12][13][14] resulting in the amelioration of the enhanced intrarenal Ang II contents seen during chronic Ang II infusion. ARB treatment also blocked the Ang II-mediated inhibition of renin release leading to increased circulating Ang II levels.…”
Section: Discussionmentioning
confidence: 99%
“…Intrarenal AngII is found regionally compartmentalized (24). Intact AngII is found in endosomes that are derived from receptor-mediated endocytosis.…”
Section: Local Raasmentioning
confidence: 99%
“…These results suggest that at least part of the augmented Ang II content in the kidney from Ang II-infused hypertensive rats is distributed to the RIF. Zhuo et al [59] showed that Ang II levels in renal cortical endosomes and intermicrovillar clefts are markedly increased in Ang II-infused hypertensive rats and that the increases in endosomal and intermicrovillar cleft Ang II levels were prevented by concurrent administration of candesartan. These results suggest that intracellular trafficking or accumulation of circulating and/or intrarenally formed Ang II into cortical tubular endosomes are enhanced during Ang II-dependent hypertension, and that this process is mediated by AT1 receptors.…”
Section: Renal Interstitial Function Of Angiotensin IImentioning
confidence: 99%
“…Therefore, this pathway could also lead to de novo Ang II formation and secretion into the renal interstitial space. Treatment with AT1 receptor blockers prevents the cascade involving ligand-receptor activation and internalization [59] with subsequent stimulation of angiotensinogen synthesis and release [60], leading to reductions in RIF concentration of Ang II [56] (fig. 1d).…”
Section: Renal Interstitial Function Of Angiotensin IImentioning
confidence: 99%